Fat necrosis mimicking liposarcoma in a patient with pelvic lipomatosis CT findings - (:unkn) unknown (ELSEVIER SCIENCE INC, 2003)
Pelvic lipomatosis is a rare condition characterized by an overgrowth of normal fat in the perirectal and perivesical spaces. The most important differential diagnosis is liposarcoma. We present a case of pelvic lipomatosis associated with a mass, which was diagnosed radiologically as a liposarcoma, but surgical biopsy result revealed fat necrosis. (C) 2003 Elsevier Science Inc. All rights reserved.
Keywords: pelvic lipomatosis; fat necrosis; CT; liposarcoma